An 18-Year Dataset on the Clinical Incidence and MICs to Antibiotics of Achromobacter spp. (Labeled Biochemically or by MAL-DI-TOF MS as A. xylosoxidans), Largely in Patient Groups Other than Those with CF - Claudio Neidhöfer; Christina Berens; Marijo Parčina (MDPI AG, 2022)
Achromobacter spp. are intrinsically multidrug-resistant environmental microorganisms which are known to cause opportunistic, nosocomial, and sometimes chronic infections. The existing literature yields scarcely any larger datasets, especially with regard to the incidence in patient groups other than those with cystic fibrosis. The aim of this study was to fill this gap. We present a retrospective analysis of 314 clinical and 130 screening isolates detected in our diagnostic unit between 2004 and 2021, combined with patients' demographic and clinical information (ward type and length of hospitalization), and the results of routine diagnostic antibiotic MIC determination. We found the apparent increase in prevalence in our diagnostic unit, in which cystic fibrosis patients are an underrepresented group, in large part to be attributable to an overall increase in the number of samples and, more importantly, changes in the diagnostic setting, such as the introduction of rigorous screening for Gram-negative multidrug-resistant pathogens. We found these Achromobacter spp. to be most commonly detected in urine, stool, wounds and airway samples, and found the resistance rates to vary strongly between different sample types. Intestinal carriage is frequently not investigated, and its frequency is likely underestimated. Isolates resistant to meropenem can hardly be treated.